THE EFFECT OF COMPETENCE AND WORK DIGITALIZATION ON EMPLOYEE PERFORMANCE, THROUGH THE EFFECTIVENESS OF COMMUNICATION IN THE GENERAL PART OF THE REGIONAL SECRETARIAT OF JEMBER REGENCY - Puji Wanusta Rini; Eko Budi Santoso; Trias Setyowati (Universitas KH. Abdul Chalim Mojokerto, 2026)
Facing the demands of bureaucratic reform and digital transformation in local government, the performance of Jember Regency Secretariat employees is the key to achieving excellent public services in the midst of complex administrative dynamics. Employee competency factors and work digitalization are considered to play a strategic role in improving this performance, with the effectiveness of communication as a crucial link. This study aims to analyze the influence of competence and work digitalization on employee performance, with the effectiveness of communication as an intervening variable in the Jember Regency Secretariat. This type of research uses a quantitative method with a descriptive approach, through observation, questionnaires, and literature studies. The research population is all employees of the Jember Regency Secretariat, with a sample of 109 respondents. The data was analyzed using Structural Equation Modeling (SEM) to test the direct and indirect relationships between variables. The results of the study show that competence and work digitalization have a positive and significant effect on employee performance, both directly and through communication effectiveness mediation. Competence (knowledge, skills, attitudes, motives, strategic thinking) and digitalization (SiKeren, automation) create effective communication that significantly improves the performance of Jember Regency Secretariat employees.